2019
DOI: 10.5696/2156-9614-9.24.191203
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation Options for Heavy Metal Pollution

Abstract: Background.Rapid industrialization and anthropogenic activities such as the unmanaged use of agro-chemicals, fossil fuel burning and dumping of sewage sludge have caused soils and waterways to be severely contaminated with heavy metals. Heavy metals are non-biodegradable and persist in the environment. Hence, remediation is required to avoid heavy metal leaching or mobilization into environmental segments and to facilitate their extraction.Objectives.The present work briefly outlines the environmental occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
125
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(138 citation statements)
references
References 163 publications
(86 reference statements)
1
125
0
12
Order By: Relevance
“…Numerous reports have demonstrated that in heavy metal polluted environments, microbial populations develop the ability to adapt to the high contamination levels ( Forster, 2003 ; Narendrula-Kotha and Nkongolo, 2017 ; Coelho et al, 2020 ). Nevertheless, there are concerns over heavy metal pollution from industries including mining, electroplating, dyeing, and tannery ( Shukla and Vankar, 2014 ; Kapahi and Sachdeva, 2019 ). To address the effect of heavy metal contamination, chemical methods such as ion-exchange, electrochemical treatment, and chemical precipitation have been developed to control excess heavy metals in wastewater and agricultural fields ( Shukla and Vankar, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have demonstrated that in heavy metal polluted environments, microbial populations develop the ability to adapt to the high contamination levels ( Forster, 2003 ; Narendrula-Kotha and Nkongolo, 2017 ; Coelho et al, 2020 ). Nevertheless, there are concerns over heavy metal pollution from industries including mining, electroplating, dyeing, and tannery ( Shukla and Vankar, 2014 ; Kapahi and Sachdeva, 2019 ). To address the effect of heavy metal contamination, chemical methods such as ion-exchange, electrochemical treatment, and chemical precipitation have been developed to control excess heavy metals in wastewater and agricultural fields ( Shukla and Vankar, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…These conventional methods are usually expensive and ineffective whenever heavy metal concentrations in the environment occur in very low concentrations. Therefore, the option to complement and integrate conventional methods with biological methods such as filamentous biosorption and bioaccumulation is becoming increasingly attractive ( Kapahi and Sachdeva, 2019 ). The basic and simplified laboratory process for fungal biosorption is demonstrated in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…& Arthrobacter sp., P.aeruginosa & B.subtilis, S.cerevisiae & P.aeruginosa, S.cerevisiae and B.subtilis). Biosorption by bacteria ((Bacillus), cocci (Streptococcus), filamentous (Actinomyces) and spiral (Vibrio cholera)) is an inexpensive and efficient technique to remove pollutants, like heavy metals, from wastewater [48,49]. Different species of algae are present in large amounts in marine ecosystems [50].…”
Section: Mitigation Of Heavy Metalsmentioning
confidence: 99%
“…However, current bioremediation technologies, either chemical or physical, are complex, energy-demanding and costly (Khalid et al, 2017). One of the current options studied is to find a biological solution to the problem (Kapahi & Sachdeva, 2019).…”
Section: Heavy Metal Remediationmentioning
confidence: 99%
“…Studies into bioremediation of heavy metals by microorganisms have mainly focused on the bioaccumulation of heavy metals in the cell biomass whereas post‐management of the accumulated metals is not often addressed (Kapahi & Sachdeva, 2019). While different techniques such as incineration, landfilling and recycling have been explored to find ways to manage heavy metals, an economical and environmentally sustainable disposal method is yet to be found.…”
Section: Bioremediationmentioning
confidence: 99%